Burden of febrile neutropenia in paediatric oncology: Experience from Children’s Hospital Lahore Pakistan - Ahmad, Alia; Khan, Fauzia Shafi; Shamim, Wasila; Ahmad, Aman Salman (Journal of Fatima Jinnah Medical University, 2021)
Background: Infection is the major cause of morbidity and mortality in children with cancer. Chemotherapy induced febrile neutropenia-associated mortality is much higher in low-middle-income countries than in high-income countries, emphasizing the need of prevention, early identification and timely management of infection related complications in these children. Objective of this prospective study was to analyze the burden of chemotherapy induced febrile neutropenia and to assess the leading risk factors. Patients and methods: Prospective cohort study was done in 100 patients with febrile neutropenia (fever of 38.3℃ and ANC <500) admitted in the Haematology/Oncology Department of Children’s Hospital Lahore (CHL) from July to August 2016. All the children on curative chemotherapy were included in this study and children with relapse and on palliation were excluded from this study. Risk factors including knowledge of parents and caregivers about febrile neutropenia, travel time from home to hospital and duration of symptoms at home before seeking treatment and reasons for delayed response in these children’s febrile illness, were analyzed for duration of hospital stay considered as a burden on the Haematology/Oncology Department. Data regarding their age, sex, and clinical features, baseline CBC, course of therapy, hospital stay and understanding of caregivers regarding febrile neutropenia was analyzed. The first line therapy was IV Piperacillin-Tazobactam and IV Amikacin. SPSS-16 software was used to analyze the data and a p-value of <0.05 was considered as statistically significant. Results: Total 100 patients with age ranging from <1 to 15 years were included. Male to female ratio was 1.7:1, 72% of the cases had Acute Lymphoblastic Leukaemia and 28% with solid tumors. About, 28% had last chemotherapy received in 72 hours, 30% in last week and rest in more than a week time 36% had upper respiratory tract infections, 18% gastrointestinal infections, 20% mucositis, 10% no focus found and rest 16% had other manifestations. Only 2 % presented in less than one hour of start of symptoms, 27% <24 hours, 61% in <5 days and 10% >5 days duration of symptoms. 45% had Hb <8 gm/dL, 33% had platelets <50,000 mm3, and 54% had WBC <1000 and 63% had ANC <100. 29% presented with the first episode while 51% had 3 or more febrile neutropenia episodes. 28% cases stayed 1 hour distance from CHL while 72% had to travel >1-5 hours to reach the primary treatment center. 66% received paracetamol at home, 17 had oral antibiotics while 17% had no treatment before reaching hospital. Only 19% caregivers had adequate awareness regarding adequate management of febrile neutropenia, 72% had some understanding while 9% had no knowledge about febrile neutropenia. 46% had financial issues, 41% were unaware while, 13% showed negligence in seeking treatment. Only 2 patients stayed for a day, 46% stayed for 5 days and 48% for more than 5 days. Conclusion: Febrile neutropenia episodes accounted for 25% of monthly admissions of the Haematology/Oncology Department of Children’s Hospital Lahore. Majority of these caregivers had inadequate basic knowledge of standard management of febrile neutropenia aggravated by increased travel time from their homes to the hospital.